Comparative Analysis of Halal Food Product Competitiveness in Southeast Asia: A Case Study of Singapore and Thailand - Aisyah Amini; Imsar Imsar; Budi Dharma (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to analyze the comparison of halal food products between Singapore and Thailand in the context of competitiveness in Southeast Asia. This research uses a qualitative approach, and with a literature study, the analysis tool is a comparative study or comparative study is a study comparing two or more conditions, events, activities, programs and others. The results of the analysis show that Singapore tends to target a wider global market, while Thailand has a focus on the regional market. Both are active in marketing their halal food products at the global level. In terms of Different Marketing Strategies, Singapore stands out in innovative and modern marketing, while Thailand emphasizes local wisdom and traditional wealth in its marketing strategy, In terms of consumer awareness of halalness is increasing in both countries, creating growth opportunities for the halal food industry. Both countries place importance on halal certification to build trust with Muslim consumers, which can influence purchasing decisions and company competitiveness. Thailand is arguably superior in providing halal culinary, because they have quite a lot of Muslim citizens compared to Singapore, and also for the production of culinary sales Thailand is more numerous and diverse, they have many traditional foods that are sold and produced in their market.